2021
DOI: 10.3390/jcdd8120161
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Induced Thrombocytopenia under Mechanical Circulatory Support by Large Impella for Acute Cardiogenic Shock

Abstract: Despite the critical feature of heparin-induced thrombocytopenia (HIT) for patients on mechanical circulatory support, reports on its incidence and outcome are still scarce. Thus, we report on clinical features of HIT in patients under Impella 5.0 or 5.5 (Abiomed Inc., Danvers, MA, USA) (Impella 5+) support for acute cardiogenic shock (CS) by focusing on observed thrombotic events. Between November 2018 and December 2020, a total of 56 consecutive patients were enrolled in a single-center retrospective study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
2
12
1
Order By: Relevance
“…Additionally, the TTR reported in our study is nearly identical to the TTR observed with systemic heparin reported by Wood et al Major bleeding requiring either transfusion or vascular surgery has been reported in 9%–29% of patients treated with an Impella device and heparin‐based anticoagulation 24,26 . While difficult to draw direct comparisons between our cohort and with previously published data surrounding heparin‐based anticoagulation, it appears that the bleeding rates observed in our series are comparable to formerly published data 24,27 . Third, the use of tPA was at the discretion of the multi‐disciplinary team without pre‐specified triggers to initiate a tPA purge solution.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, the TTR reported in our study is nearly identical to the TTR observed with systemic heparin reported by Wood et al Major bleeding requiring either transfusion or vascular surgery has been reported in 9%–29% of patients treated with an Impella device and heparin‐based anticoagulation 24,26 . While difficult to draw direct comparisons between our cohort and with previously published data surrounding heparin‐based anticoagulation, it appears that the bleeding rates observed in our series are comparable to formerly published data 24,27 . Third, the use of tPA was at the discretion of the multi‐disciplinary team without pre‐specified triggers to initiate a tPA purge solution.…”
Section: Discussionsupporting
confidence: 87%
“…24,26 While difficult to draw direct comparisons between our cohort and with previously published data surrounding heparin-based anticoagulation, it appears that the bleeding rates observed in our series are comparable to formerly published data. 24,27 Third, the use of tPA was at the discretion of the multi-disciplinary team without pre-specified triggers to initiate a tPA purge solution. However, most of the tPA purge solution use only occurred after declines and rises in purge rates and pressures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…supported patients noted a 10.7% incidence of HIT; however, confirmatory functional assay results were not reported. 12 In our population, no patient developed functional assay/SRA-confirmed HIT despite many patients experiencing a platelet drop ≥50% of baseline and 6.4% of patients having a positive PF-4 ELISA.…”
Section: Discussionmentioning
confidence: 67%
“…Postoperative management after Impella 5+ follows as we described before ( 9 , 10 ). Briefly, all parameters displayed in Impella monitor, e.g., Impella setting, Impella flow, purge pressure, purge flow rate, and placement signal, were documented every 3 h. All patients underwent chest X-ray evaluation every day to examine the position of the Impella pump.…”
Section: Methodsmentioning
confidence: 99%
“…However, both anticoagulation agents were regulated appropriately in case of significant bleeding, i.e., major bleeding. In the case of heparin-induced thrombocytopeniaII, argatroban was administrated instead of heparin ( 10 ). For the evaluation of whole organs, blood gas analysis was routinely performed several times per day.…”
Section: Methodsmentioning
confidence: 99%